Технические средства и способы тушения пожаров - Авакимов С. С. Сергей Сергеевич; Булгаков В. П. Виктор Павлович; Бушуй М. И. Михаил Иванович; Тараканов Н. Д. Николай Дмитриевич; Иванов Б. П. (Москва, Энергоиздат, 1981)
Авторы указ. на обороте тит. л.